ALTERED GROUND REACTION FORCE DURING COUNTER MOVEMENT JUMPS IN PREVIOUSLY INJURED PROFESSIONAL FOOTBALL PLAYERS. Issue 4 (1st February 2017) - Argemi, Ruben; Elverdin, Julio; Gallo, Pablo Ortega
Abstract : Background: Sports injuries produce changes in movement characteristics, which can be measured qualitatively and quantitatively in the ground reaction force. Objective: To characterize the strength curve of a counter movement jump (CMJ) in professional footballers who were suffering from sports injuries. Design: Case-control study. Setting: Professional footballers of Club Atlético Boca Juniors. Participants: 32 players suffering from sports-related ankle, knee and muscle injuries, who were tested during the first week that they were able to jump, and 52 as control group, who were tested during preventive medical controls. Main Outcome Measurements: We analysed 5 stages of the force curve during CMJ: 1. Starting movement, 2. Start of eccentric contraction, 3. Eccentric contraction, 4. Peak eccentric, 5. Peak concentric, and rate of force development (RFD). In areas 1, 2 and 3 asymmetry was examined qualitatively (curve shape ), in zones 4 and 5, quantitatively (>5%). Results: All of injured players showed asymmetry versus 48% in control group (p<0.05), 85% of injured players showed deficits in zone 4 (16.5% in peak force vs 11, 6% in control; p<0.05). Asymmetry of RFD in players with ankle and knee injuries was 26% and 14%, respectively, while those with psoas injuries presented inverted asymmetry(less force in non injury leg). Players with ankle injuries showed asymmetry in zones 1–4 and knee injuries in zones 1–5 (73% and 85% of the cases, respectively). Players treated surgically for knee injuries (ACL and menisci) demonstrated asymmetry in zones 4 and 5 in 100% of the cases. Players with adductor and hamstring injuries displayed asymmetry in zones 4 and 2–3, respectively (100% of cases for both). All players were symmetrical at return to sports. Conclusions: The force plate is a device that allows the characterization of function in sports injuries during the rehabilitation process, and help establish parameters for the return of the athlete to a normal athletic life.